Differential Expression of AMPA Subunits Induced by NMDA Intrahippocampal Injection in Rats - Fachim, Helene A.; Pereira, Adriana C.; Iyomasa-Pilon, Melina M.; Rosa, Maria L. N. M. (Frontiers in Neuroscience, 2016)
Glutamate is involved in excitotoxic mechanisms by interacting with different receptors. Such interactions result in neuronal death associated with several neurodegenerative disorders of the central nervous system (CNS). The aim of this work was to study the time course of changes in the expression of GluR1 and GluR2 subunits of glutamate amino-acid-3-hydroxy-5-methyl-isoxazol-4-propionic acid (AMPA) receptors in rat hippocampus induced by NMDA intrahippocampal injection. Rats were submitted to stereotaxic surgery for NMDA or saline (control) microinjection into dorsal hippocampus and the parameters were evaluated 24 hours, 1, 2 and 4 weeks after injection. The extension and efficacy of the NMDA-induced injury were evaluated by Morris water maze (MWM) behavioral test and Nissl staining. The expression of GluR1 and GluR2 receptors, glial fibrillary acidic protein (GFAP) and neuronal marker (NeuN) was analyzed by immunohistochemistry. It was observed the impairment of learning and memory functions, loss of neuronal cells and glial proliferation in CA1 area of NMDA compared with control groups, confirming the injury efficacy. In addition, NMDA injection induced distinct changes in GluR1 and GluR2 expression over the time. In conclusion, such changes may be related to the complex mechanism triggered in response to NMDA injection resulting in a local injury and in the activation of neuronal plasticity.